Environmental analysis and ecosystemic design. Survey, critical issues and application solutions - Chiara Catalano; Andrea Balducci (Agathón)
Fragmentation, environmental degradation, and habitat loss, due to urbanization and the consequent development of infrastructure, put a great deal of pressure on biological diversity and the functioning of ecosystems. In the coming decades, the ecological footprint of urban areas is set to increase, exacerbating the effect of climate change. In this context, urban development projects represent an excellent opportunity to experiment and implement new solutions which promote biodiversity. This work investigates, on the one hand, how aware designers are of solutions that aim to support biodiversity, and on the other hand, how spatial analysis and the adoption of parametric procedures can optimize cooperation between ecologists and designers from the early design stages.